Diversity and Identification of Yeasts Isolated from Tumultuous Stage of Spontaneous Table Grape Fermentations in Central China - Ye, D.-Q.; Sun, Y.; Song, Y.-Y.; Ma, X.-L.; Ren, X.-N.; Gong, X.; Liu, Y.-L. (South African Journal of Enology and Viticulture, 2018)
Table grapes are of increasing interest for wine production in China. In this study, 480 yeast isolates were isolated from the tumultuous stage during the spontaneous fermentation of six table grape varieties, which were cultivated in an ecological environment that was not industry-influenced, in Central China. The 26S rDNA D1/D2 domain sequence analysis was more efficient for yeast species identification than the 5.8S-ITS region RFLP analysis in the present study. All the tested strains belonged to nine species from six genera: Hanseniaspora guilliermondii, H. opuntiae, H. uvarum, Pichia terricola, Kazachstania hellenica, K. zonata, P. occidentalis, Saccharomyces cerevisiae and Zygosaccharomyces bailii. The yeast species and populations differed notably among the grape varieties. S. cerevisiae was found in the samples of four grape varieties (Vitis amurensis, Iona, Moldova and V. davidii), but not detected in Cuihong and Alimandeng Rose. Interdelta sequence fingerprinting analysis was used to discriminate between 128 S. cerevisiae isolates. Eight S. cerevisiae genotypes (G1 to G8) were distinguished. Genotypes G1, G2, and G3 were the most dominant strains, accounting for 32.03%, 24.22% and 28.13% of the isolates respectively. This study shows the diversity of yeast species associated with spontaneous fermentations of different table grape varieties grown in an ecological environment without any wine industry effect or footprint.